Effect of beta blocker therapy following myocardial infarction in optimally treated patients in the reperfusion era – a Danish, nationwide, and registry-based cohort study. (25th November 2020) - Holt, A; Zareini, B; Rajan, D; Schou, M; Gislason, G.H; Schjerning, A.M; McGettigan, P; Blanche, P; Torp-Pedersen, C; Lamberts, M
Abstract: Background and purpose: European and American cardiovascular treatment guidelines advocate for two and three years of beta-blocker (BB) treatment, respectively, following myocardial infarction (MI). Contemporary continued efficacy of longer-term use of BB in stable coronary artery disease has been debated in the era of reperfusion. We aim to investigate the cardio-protective effect associated with BB treatment in patients following MI. Methods: Using nationwide databases, we included optimally treated patients with first-time MI undergoing coronary angiography (CAG) or percutaneous coronary intervention (PCI) during admission and treated with both acetyl-salicylic acid and statins post-discharge between 2003 and 2017. Patients with prior history of MI, BB use or any other possible indication or contraindication for BB treatment (heart failure, cardiac arrhythmias or procedures, asthma, chronic obstructive pulmonary disease) were excluded. Continued BB exposure was defined as two redeemed prescriptions within the first 180 days following discharge, one of them within 90 days. Follow-up began 180 days following discharge in patients alive and with no further cardiovascular events or procedures prior. Patients were followed for a maximum of three years. Primary outcomes were cardiovascular death and recurrent MI in patients stratified by BB treatment using adjusted Cox regression models. Results: A total of 27, 068 patients optimally treated for MI were included (57% acute PCI, 26% sub-acute PCI, 17% CAG without intervention). At study start 180 days following MI, 79% of the patients were on BB treatment (median age 61 years, 75% male) and 21% were not (median age 62 years, 69% male). Cumulative incidence of cardiovascular death and recurrent MI did not differ significantly comparing patients on BB treatment with patients not on BB treatment (Figure). In multivariable analyses, BB treatment was associated with a similar risk of cardiovascular death and recurrent MI compared to the patients not receiving BB treatment (hazard ratios with [95% confidence intervals] correspondingly; 0.89 [0.68–1.17] and 1.02 [0.89–1.18]) (Figure 1). When stratifying the cohort according to calendar year and type of procedure during admission, we found similar results as the main analysis. No interaction for sex was found. Conclusions: In this nationwide cohort study of optimally treated patients following MI at 180 days in the reperfusion era, we found a very good prognosis with only 1.2% suffering cardiovascular death and 4.7% suffering a recurrent MI within three years. In total 79% of patients were receiving BB treatment, but we found no difference suggesting BB to be associated with an improved cardiovascular prognosis. These findings challenge current clinical practice and guideline recommendation, suggesting that the role of long-term BB use may be obsolete among optimally treated MI patients. Further investigations, preferably a randomized trial, are warranted. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Ib Mogens Kristiansens Almene Fond, Snedkermester Sophus Jacobsen og Hustru Astrid Jacobsens Fond